Uwolnienie monografii pedagogicznej - Kowzan , Piotr (Studia Edukacyjne, 2021)
The aim of the article is to free the pedagogical monograph method from the limitations imposed on it in the mid-20th century. Descriptions of this research method will be related to the specificity of the context and the needs it was supposed to satisfy at the time. Changes in the socio-economic and technological context will justify the removal of the existing limitations from the pedagogical monograph. As a result of this analysis, I propose ways to use this research method in contemporary pedagogy.